Proposed Strategy for a Regional Exchange Rate Arrangement in Post-Crisis East Asia - Kawai, Masahiro (World Bank, Washington, DC, 2014)
After discussing major conceptual, and empirical issues relevant to the exchange rate policies of East Asian countries, the authors propose a regional exchange rate arrangement designed to promote intra-regional exchange rate stability, and regional economic growth. They argue that: 1) For developing countries, exchange rate volatility tends to significantly hurt trade and investment, making it inadvisable to adopt a system of freely floating exchange rates. 2) Given the high share of intra-regional trade, and the similarity of trade composition in East Asia, exchange rate policy should be directed toward maintaining intra-regional exchange rate stability, to promote trade, investment, and economic growth. 3) the current policy of maintaining exchange rate stability against U.S. dollar as an informal, uncoordinated mechanisms for ensuring intra-regional exchange rate stability is sub-optimal. A pragmatic policy option - conducive to a more robust framework for cooperation in monetary, and exchange rate policy - wold be a coordinated action to shift the target of nominal exchange rate stability, to a basket of tri-polar currencies (the U.S. dollar, the Japanese yen, and the Euro). This alternative would better reflect the region's diverse structure of trade, and foreign direct investment. The authors envision no rigid peg. Instead, at least initially, each country could choose its own formal exchange rate arrangement - be it currency board, a crawling peg, or a basket peg with wide margins. At times of crisis, the peg might be temporarily suspended, subject to the rule that the exchange rate would be restored to the original level as soon as practical. Only in extreme circumstances, would the level be adjusted to reflect new equilibrium conditions.